2008
DOI: 10.1163/156853108x364226
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualising the Network Society in Malaysia

Abstract: Various studies have confirmed the existence of a network society in Malaysia. They generally identify its presence through aggregated individual level attributes, such as possession and usage of computer and the Internet, access to computer and the Internet, and benefits received by the network societal members. This society is widely said to be the outcome of the Malaysian government's efforts to counter increasing challenges and impacts of globalisation and ICT waves since the 1990s; in particular, the digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…Several studies were conducted and reported by Chan (2004;2007;2008;2015), Chan and Mohamad Zaki (2008), Chan, Halimaton Saadiah and Sarah (2011) and Chan et al (2010;2015) on social networks, focusing in Malaysia. Initially, Chan's utilisation of the network method led to her discovery of big business formation (patterning of the business group structure) in Malaysia that were based on formal organisational networks (i.e.…”
Section: Issue and Significance Of Governance Network For Effective mentioning
confidence: 99%
“…Several studies were conducted and reported by Chan (2004;2007;2008;2015), Chan and Mohamad Zaki (2008), Chan, Halimaton Saadiah and Sarah (2011) and Chan et al (2010;2015) on social networks, focusing in Malaysia. Initially, Chan's utilisation of the network method led to her discovery of big business formation (patterning of the business group structure) in Malaysia that were based on formal organisational networks (i.e.…”
Section: Issue and Significance Of Governance Network For Effective mentioning
confidence: 99%